STUDENTS’ ABILITY IN USING SUBJECT-VERB AGREEMENT - N. Erna Marlia Susfenti (FKIP, Universitas Banten Jaya, 2020)
This research was aimed at investigating the Students’ Ability in Using Subject- Verb Agreement and the error made by the students in using subject-verb agreement. The writers was used the deductive approach to minimize the errors on learning grammar process and improving their ability in using subject-verb agreement. The students ability in using subject-verb agreement was categorized into the poor categories with 17 students and followed by very poor categories with 8 students from 34 students are there in the class. This research also found some causes of the students error while learning the grammar structure especially subject-verb agreement. The error occurred while learning subject verb agreement was on intralingua error like, false analogy and misanalysis.